An Introductory Review Expert Systems in Mining Engineering - R. V. Ramani (The National Institute for Occupational Safety and Health (NIOSH), 1989)
"In a 1985 seminar, we were told that over-optimism abounds in Artificial Intelligence (AI), that AI is neither a science nor a technology yet, and that we will be both exhilarated and disappointed with AI. In fact, even today, there is no single accepted definition of AI; however, certain features have been identified by AI researchers as essential to consider an entity (e.g. machine or program) to be intelligent. According .to Shank (1987), these features include communication (to be able to communicate with), internal knowledge (knowledge about itself), world knowledge (awareness and knowledge about the world outside), intentionality (knowing what one wants and a plan to seek it, ie. goal seeking behavior), and creativity (being adaptable to changing conditions). None of these figures would individually define intelligence; however, each would be a part of intelligence in its own way.The prospects for the development of entities with AI have never been as good as they are now. The combination of advancements in computer hardware and .software along with new insights into the ways in· which we store knowledge and use it for problem solving has enhanced the potential for the creation ~f intelligent entities. After some unbounded optimism of a major breakthrough in the fifties and frustrating disappointments in the two following decades, it appears now that AI has emerged from research labs to industrial practice. This is confirmed by the growing number of repeat applications of AI in business and industry to the extent that AI can now be considered a technology.AI applications are categorized into several distinct areas such as Natural Language Processing, Speech Recognition and Synthesis, Expert Systems, Robotics, Machine Vision, etc. Of these practical realizations, Expert Systems (ES) has the greatest potential for meeting the decision-making needs of the manager in the ever-growing complex scoio-technical systems. Prof. Feigenbaum, an expert and leader on expert systems, has defined Expert System as"" ... an intelligent computer program that uses knowledge and inference procedures to solve problems that are difficult enough to require significant human expertise for their solution. Knowledge necessary to perform at such a level, plus the inference procedures used, can be thought of as a model of the expertise of the best practitioners of the field."""